Efecto de los cambios de la presión parcial arterial de oxígeno y en la glucosa sanguínea sobre la variabilidad de la frecuencia cardiaca - Carrasco Sosa, Salvador (Universidad Autónoma Metropolitana, 1999)
Presentation. This thesis belongs to the scope of human physiology. It deals with the functional relationship between the autonomic nervous and the cardio-respiratory systems. Specifically, it treats the effects of some experimental maneuvers over the variability of cardiovascular parameters. Each of the selected maneuvers has been a well-established research area for decades. An original aspect of the thesis is the study of the effect that the maneuvers have over the variability of the cardiovascular parameters by the application of a set of engineering techniques; in particular, using digital signal processing for the temporal, spectral and non-linear dynamics analysis. The figure presents the different works developed in this thesis, as well as their main contributions. Background. The heart rate variability (HRV) is an efficient quantitative index of the autonomous nervous system activity. Its study has provided significant contributions to the physiology and the clinical fields. In physiology, it has allowed a deepest study of the cardiovascular control mechanisms. In clinical, the HRV has been used as a powerful predictor of mortality after cardiovascular sickness. Even more, it has shown that respiratory, renal, digestive, endocrine and neurological sicknesses provoke alterations in the autonomous nervous system function. Although a task force recently (1996) tried to standardize the techniques and methodologies, there is still confusion on the correct utilization of them. Objectives. Two specific types of problems are treated in this thesis, methodological and physiologic. In this order, the methodological goals were: To compare the behavior of the HRV parameters (low and high frequency components, and its relationship) by three spectral estimators: the Fourier transform, the smoothed periodogram, and by auto-regressive modeling, during six experimental conditions: lying, controlled breathing, standing, cycling exercise, recovery, and weight lifting exercise. To compare the HRV obtained from the RR intervals and the cardiotachogram, in the time and frequency domain, during the five experimental maneuvers, in order to assess if they can be interchanged. To compare the Finapres numeric and analog outputs, to determine the similarity between the temporal and spectral parameters of the systolic and diastolic pressure variability for the five experimental maneuvers. To compare the HRV determined from the RR (ECG) and PP (arterial pressure waveform) intervals, in order to evaluate the similarity between their temporal and spectral parameters for the five experimental maneuvers. To compare the discriminative capacity and the physiological appropriateness of different integration-normalization ranges for the spectral HRV parameters during the five maneuvers, and to verify the similarity of the response pattern of the individuals’ heart rate variability, and in consequence, of the autonomous nemous system. Determine the repeatability of the temporal and spectral heart rate variability parameters for the same individual group in three different days. On the physiological aspects, the goals were, o Using the analysis of the heart rate and other cardiovascular parameters variability, to study the effect over the autonomous nervous system activity by experimental situations such as: - Oral glucose administration (hyperglycemic stimulation), - Insulin subcutaneous administration (hypoglycemic stimulation). - 12% oxygen mix respiratory administration (hypoxic stimulation), - 100% oxygen mix respiratory administration (hyperoxic stimulation). To perform the five mentioned maneuvers to show that the leR ventricular systolic intervals, the ejection time, the electromechanical systole, the pre-ejection period, the preejection period/ejection time ratio, the diastolic time, and the Hill index have beat-by-beat variability, and that there is a respiratory and heart rate influence over this variability. Also the systolic volume and cardiac output variability obtained by cardioimpedance, will be investigated. Method. The studies were performed on healthy volunteers, of both sexes. The number of subjects for each of the studies varied form 10 to 15. For the methodological test, the protocol was based on the maneuvers: lying, controlled breathing, exercise, and recovery. The ECG, the respiratory amplitude, and the blood pressure were: recorded and digitized. The signals were processed for the time and spectral analysis. This methodology was used only in one of the physiological studies. In four more, the experimental maneuvers were the administration of glucose (hyperglycemia), insulin (hypoglycemia), 100% oxygen (hyperoxemia), and 12% oxygen (hypoxemia). The recorded signals were the same as previous, but in these cases, the following analyses were added: toneentropy, return maps, approximate entropy, and the baroreceptor sensibility by two methods. For the last study, cardiovascular parameter variability, the ear pulse, phonocardiogram, and the derivative of cardioimpedance signal were recorded besides the ECG, breathing and blood pressure. The five-maneuver protocol was employed. The processing included temporal and spectral analysis, tone-entropy, return maps, approximate ntropy, and the baroreceptor sensibility by two methods. Results. During the thesis development, the different findings produced the works listed, together with the most important results: Performance comparison of three spectral estimation tec.hniques for the HRV analysis. The comparison of the three frequency components, computed by three different spectral estimation techniques did not show significant statistic differences for five of the six conditions. Comparison of the heart rate variability parameters obtained from the RR interval and the cardiotachogram. The statistical difference between the HRV means for both methods can be explained by a systematic sub-estimation error by the cardiotachogram. he low and high frequency components, as well as its ratio, are interchangeable between the methods, as they had a high correlation and they did not present significant statistical differences for any maneuver. Comparison of the blood pressure variability parameters obtained from the Finapres numeric and analog outputs. In all the experimental conditions, the means of the four spectral parameters, for both the systolic and diastolic pressures did not present statistical differences; high correlation coefficients, and very low mean differences and concordance limits were found. Comparison of the heart rate variability parameters obtained from the electrocardiogram and the blood pressure waveform Only for the lying, controlled-breathing, and recovery maneuvers, the frequency domain heart rate variability parameters computed from the RR intervals and from the PP intervals (obtained by the Finapres), were interchangeable. HRV parameters behavior in healthy individuals during a five-maneuver protocol. The spectral parameters that discriminate at least among consecutive maneuvers, and in consequence, that presented a distinctive behavior during the protocol were the wide range total power spectrum, and the low- and mid-frequency components for both integrationnormalization bands. The very low-frequency component had a spectral power higher to 50% for exercise. The very high-frequency component, although it was present in all maneuvers, attained its maximum value for exercise (7.6%). In general, the two kinds of frequency components (normalization in the standard and wide bands) presented the same tendency among the maneuvers. Repeatability of the heart rate variability pattern response to the standard maneuvers. The mean of each temporal and spectral analysis estimator did not show significant statistic differences for the three days Hyperglycemia effect over the cardiovascular variability parameters. The spectral analysis of the RR interval variability showed: significant reductions of partial low, mid, and standard low-frequency components; a significant increment of the standard high-frequency component together with an increment on its frequency; a significant decrease of the low/high ratio. 0 Hypoglycemia effect over the cardiovascular variability parameters. The spectral analysis of the RR interval variability showed: significant increments of partial low and standard low-frequency components, plus a frequency shift to the left; significant decrease of the total spectral power, the standard high-frequency component, together with an increase on its central frequency; significant increase of the low/high ratio. Hyperoxic effect over the cardiovascular variability parameters. The spectral analysis of the RR interval variability presented: significant reductions of the normalized partial low and standard low-frequency components; significant increase of the high-frequency component, and of total power; a significant decrease of the low/high ratio. Hypoxic effect over the cardiovascular variability parameters. The spectral analysis of the RR interval variabi1it.y showed: significant increment of the normalized standard low-frequency components, with a left shift of the frequency; significant decrease of the standard high-frequency component; a significant increment of the low/high ratio, and the log spectrum slope. Cardiovascular parameters’ variability in the performance of five experimental maneuvers. - Temporal analysis. The maneuvers had effect over the dispersion of the cardiovascular parameters studied. The controlled breathing increased the ejection time and diastolic time variability. For the standing stage, the diastolic time variability decreased and the systolic pressure variability increased. During exercise, the diastolic time, the pre-ejection period, and the ejection period, and the ejection time variability decreased, while an increment of the electromechanical systole, the systolic volume, the cardiac output, and the blood pressure variability was observed. - Spectral analysis. The low/high ratio of most of the cardiovascular variables is reduced for controlled breathing. For the standing stage, the low/high ratio increases in such variables as the diastolic time, the electromechanical systole, and the diastolic pressure, and its reduced for the systolic pressure. During exercise the standard low/high ratio increases, while the wide lodhigh ratio decreases for most of the cardiovascular variables. - Log power - log frequency analysis. For most of the cardiovascular variables, the maneuvers diminish the regression slope with an increment of the intercept. Exercise is the maneuver with the largest changes. - Tone-entropy analysis. Only some of the variables presented changed. For controlled breathing, the tone decreased with an increment in the entropy for the electromechanical systole and the diastolic time. For the standing stage, there is an increment on the tone and a reduction on the entropy for the electromechanical systole, the systolic volume, the cardiac output, the contractility indexes, and the diastolic pressure. During exercise, the tone increases with an entropy decrement for the pre-ejection period and the diastolic time; there is a reduction on the tone with the correspondent entropy increment for the electromechanical systole, the systolic volume, the cardiac output, the contractility indexes, and the systolic pressure. Return maps analysis. The regularity of cardiovascular variables increases throughout the maneuvers. This happens for most of the variables under controlled breathing, for the ejection time, the pre-ejection period, and the contractility indexes for standing, and the ejection time, the pre-ejection period, and the diastolic interval for exercise Approximate entropy. During controlled breathing, entropy decreases for the ejection time and the electromechanical systole, while increasing for the pressures. In standing, entropy decreases for the cardiac output, and increases for the ejection time, the preejection period, and the diastolic time. Exercke promotes the entropy of most of the cardiovascular variables. Conclusions. According to the results obtained during these studies, The three spectral estimators had a similar behavior. It is shown that the beat-by-beat heart rate data computed by the cardiotachograph are indistinct, for both the temporal and spectral analysis, from those obtained from the processing of the R-R interval, throughout all the utilized procedures. There is a strong degree of agreement among the arterial pressure variability temporal and spectral parameters, as obtained from both Finapres outputs for the five experimental maneuvers. The beat-by-beat heart rate data computed by the Finapres are not interchangeable with those obtained from ECG analysis, for any of the utilized procedures. It is shown that a series of well-defined maneuvers determine a typical behavior on some of the temporal and spectral parameters of the HRV. The temporal and spectral estimators of the heart rate variability, under the five imposed conditions, are repeatable, at least for three days. The hyperglycemic estimulation determines the inc.rease of the parasympathetic activity over the SA node, as indicated by the spectral parameters of the R-R interval. This is not related to respiratory center influence or the mild reduction of the autonomic sympathetic influence over the vascular smooth muscle (reduction of the diastolic pressure). The hipoglycemic estimulation determines a small. increment of the sympathetic and inhibition of the parasympathetic influences over the SA node, as indicated by the temporal, spectral, and tone-entropy analysis parameters. The hyperoxic estimulation determines an increase of the parasympathetic and reduction of the sympathetic influences on the SA node, without change of the autonomic flow to the arteriolar muscle, as indicated from the temporal and spectral indexes. 0 The hypoxemic estimulation determines the increase of the sympathetic activity, together with a concomitant reduction of the parasympathetic influence over the SA node and the sympathetic influence over the arteriolar muscle, as, indicated by the temporal, spectral and tone-entropy indexes. 0 The cardiovascular variables present a beat-to-beat variability. A major part of it is established by the RR variability, that is, the sympatho-vagal balance influences the variability of the rest of the cardiovascular parameters. Respiration influences through central, autonomic and peripheral, or mechanical mechanisms. The variability is modified with the maneuvers used in the study in a deterministic way, as there exist specific response patterns as shown with the indexes derived from temporal, spectral, log-power, tone-entropy, return maps, and approximate entropy analyses.; Presentación. La tesis queda enmarcada dentro del ámbito de estudio de la fisiología humana, Trata de la interacción funcional entre los sistemas nervioso autónomo y cardiorrespiratorio. En forma específica, aborda los efectos de algunas maniobras experimentales sobre la variabilidad de parámetros cardiovasculares. Cada una de las maniobras seleccionadas es una línea de investigación bien definida, cuyo inicio se remonta varias décadas atrás. Un punto novedoso de la tesis consiste en el estudio de los efectos de la maniobra sobre la variabilidad de parámetros cardiovasculares, por medio de la a.plicación de un conjunto de técnicas ingenieriles; sobresalen el procesamiento digital de señales para la realización de los análisis temporal, espectral y los de dinámica no lineal. En la figura se presentan los trabajos desarrollados en la tesis, con la principal aportación para cada uno de ellos. Antecedentes. La variabilidad de la frecuencia cardiaca (VFC) es un marcador cuantitativo eficiente de la actividad del sistema nervioso autónomo. Su estudio ha tenido aportaciones significativas en los campos de la fisiología y la clínica. En la fisiología se ha profundizado sobre todo en los mecanismos de control cardiovascu1a.r. En la clínica el análisis de la VFC es un poderoso predictor del riesgo de mortalidad post - enfermedad cardiovascular. Más aún, ha mostrado que enfermedades respiratorias, renales, digestivas, endócrinas y neurológicas, cursan con alteración en la función del sistema nervioso autónomo. A pesar de los esfuerzos hechos recientemente (1996) por un comité de expertos para estandarizar las técnicas y metodologías de estudio de la VFC, todavía prevalece hoy en día, una gran confusión acerca de la adecuada utilización de las mismas. Objetivos. La tesis aborda dos tipos específicos de problemática, metodológica y fisiológica. Así fueron objetivos metodológicos: Comparar el desempeño de indicadores de la VFC (componentes de baja frecuencia, de alta frecuencia y su relación) por tres técnicas de estimación espectral, la transformada discreta de Fourier, el periodograma promediado y por modelado autorregresivo, en las condiciones experimentales: acostado, respiración controlada, parado, ejercicio en bicicleta, recuperación y ejercicio con pesas. Comparar las variabilidades de la frecuencia cardiaca obtenidas a partir de los intervalos RR y del cardiotacograma, tanto en el dominio del tiempo como de la frecuencia, en las cinco maniobras experimentales, con la finalidad de asegurar la intercambiabilidad entre los dos métodos. 0 Comparar la salida numérica y analógica del Finapres para valorar el grado de semejanza entre los parámetros temporales y espectrales de las variabilidades de las presiones sistólica y diastólica en las cinco maniobras experimentales. 0 Comparar las variabilidades de la frecuencia cardiaca obtenidas de los intervalos RR (ECG) y PP (onda de presión arterial) para valorar el grado de semejanza entre las respectivas series de intervalos, tanto en el dominio del tiempo como de la frecuencia, en cinco maniobras experimentales. Comparar la capacidad discriminativa y adecuación fisiológica de rangos distintos de integración - normalización de los indicadores espectrales durante cinco maniobras y verificar la existencia de un patrón similar de respuesta entre los sujetos de la VFC, y por tanto de la actividad del sistema nervioso autónomlo. 0 Determinar la repetibilidad de los indicadores temporales y espectrales de la VFC a un mismo grupo de sujetos en tres días. Con relación a los fisiológicos. 0 Estudiar mediante el análisis de la VFC y de otros parámetros cardiovasculares, los efectos que sobre la actividad del sistema nerviosos autónomo determinan situaciones experimentales tales como: La administración oral de glucosa (estímulo hiperglucémico). - La administración subcutánea de insulina (estímulo hipoglucémico). - La administración de una mezcla de oxígeno al 100% (estímulo hiperoxémico). - La administración respiratoria de una mezcla de oxígeno al 12% (estímulo hipoxémico) - Demostrar que los intervalos sistólicos del ventriculo izquierdo, tiempo de eyeccion, sístole electromecánica, periodo de pre - eyección, relación periodo de pre - eyección / tiempo de eyección, tiempo diastólico, e índice de Hill presentan variabilidad latido a latido, influida por la respiración y la frecuencia cardiaca. Además se pretende corroborar las variabilidades del volumen sistblico y del gasto cardiac0 obtenidas por la cardioimpedancia. Método. Los estudios se llevaron a cabo en voluntarios sanos de ambos sexos. El número de sujetos para cada uno de los estudios varió de 10 a 15. En los trabajos metodológicos se aplicó un protocolo que consta de las maniobras: acostado, respiración controlada, ejercicio y recuperación. Se registró y adquirió el ECG, la amplitud respiratoria y la presión arterial. Las señales se procesaron por los análisis temporal y espectral. En uno de los estudios fisiológicos se empleó la anterior metodología, en los otros cuatro las maniobras experimentales heron la administración de: glucosa (hiperglucemia), de insulina (hipoglucemia), de oxígeno al 100% (hiperoxia) y de oxígeno al 12% (hipoxia). En estos se registraron las tres señales ya mencionadas, pero se agregó el análisis tono - entropía, mapas de retorno, entropía aproximada y sensibilidad de los barorreceptores por dos métodos En el último estudio, variabilidad de parámetros cardiovasculares, se agregaron al registro del ECG, respiración y presión arterial, la onda de pulso en la oreja, el fonocardiograma y la derivada de la onda de cardioimpedancia. El protocolo empleado he el de cinco maniobras. El procesamiento incluyó los análisis temporal, espectral, tono - entropía, mapas de retorno, entropía aproximada y sensibilidad de los barorreceptores por dos métodos. Resultados. Conforme avanzó el desarrollo de la tesis, los hallazgos obtenidos dieron lugar a los trabajos que a continuación se enumeran, junto con los resultados más sobresalientes. Comparación del desempeño de tres técnicas de estimación espectral para el análisis de la VFC. La comparación de los tres componentes, computados por las tres técnicas de estimación espectral, no mostró diferencias estadísticamente significativas para cinco de las seis condiciones. Comparación etre parámetros de la VFC obtenidos del intervalo RR y del cardiotacograma. La diferencia estadística entre las medias de la WC por los dos métodos es debida a la existencia de un error sistemático de subestimación del cardiotacógrafo. Los componentes de baja, alta y su relación, resultaron intercambiables entre los métodos, ya que heron altamente correlacionables, y no mostraron diferencias estadísticamente significativas en ninguna de las maniobras. Comparación entre los parámetros de la variabilidad de la presión arterial obtenidos de las salidas numérica y analógica del Finapres. Los promedios de los indicadores espectrales, tanto para la presión sistólica como la diastólica heron estadísticamente no diferentes, con coeficientes de correlación muy altos, promedio de las diferencias y límites de concordancia de valor muy pequeño, en todas las condiciones experimentales. Comparación entre los parámetros de las variabilidades de la frecuencia cardiaca obtenidas del electrocardiograma y de la onda de presión arterial. La VFC calculada a partir de los intervalos RR fue intercambiable en el dominio de la frecuencia, con la medida a partir de los intervalos PP proporcionados por el Finapres, sólo para las condiciones de acostado, respiración controlada y recuperación. Comportamiento de los parámetros de la VFC de sujetos sanos durante un protocolo de cinco maniobras. Los parámetros espectrales que al menos discriminaron entre maniobras consecutivas y que por lo tanto presentaron un comportamiento distintivo durante el protocolo heron la potencia espectral total en el rango amplio y los componentes de baja e intermedia en ambas bandas de integración - normalización. El componente de muy baja logró una potencia espectral mayor al 50% durante el ejercicio. El componente de muy alta, aunque presente en todas las maniobras, logró su máximo valor durante el ejercicio, (7.6%). En general, el comportamiento de los dos tipos de componentes (en las bandas estándar y amplia) mostró la misma tendencia de cambio entre las maniobras. 0 Repetibilidad de los patrones de respuesta de la variabilidad de la frecuencia cardiaca a las maniobras estándares. La comparación estadística de las medias de cada estimador tanto del análisis temporal como espectral en los tres días, no mostró diferencias estadísticamente significativas. 0 Efecto de la hiperglucemia sobre la variabilidad de parámetros cardiovasculares. El análisis espectral de la variabilidad del intervalo R-R mostró: disminuciones significativas de los componentes de baja parcial, intermedia y baja estándar; aumentos significativos del componente de alta estánd,w, con aumento de su frecuencia y disminución significativa de la relación bajdalta. Efecto de la hipoglucemia sobre la variabilidad de parámetros cardiovasculares. El análisis espectral de la variabilidad del intervalo K-R mostró: aumento significativo de los componentes de baja parcial y baja estándar con corrimiento de la frecuencia hacia la izquierda; disminución significativa de la potencia espectral total, del componente de alta estándar, con aumento de su frecuencia central y aumento significativo de la relación bajdalta. Efecto de la hiperoxia sobre la variabilidad de parámetros cardiovasculares. El análisis espectral de la variabilidad del intervalo R-R mostró: disminuciones significativas de los componentes normalizados de baja parcial y de baja estándar; aumentos significativos del componente de alta y de la potencia espectral total; disminución significativa de la relación bajdalta. 0 Efecto de la hipoxia sobre la variabilidad de parámetros cardiovasculares. El análisis espectral de la variabilidad del intervalo R-R mostró: aumento significativo del componente de baja estándar con corrimiento de su frecuencia hacia la izquierda; disminución significativa del componente de alta estándar; aumento significativo de la relación bajdalta y aumento en forma significativa. de la pendiente del logaritmo del espectro. Variabilidad de parámetros cardiovasculares durante la realización de cinco maniobras. - Por análisis temporal. Las maniobras afectaron los indices de dispersión de los parámetros cardiovasculares estudiados. La respiración controlada aumentó la variabilidad del tiempo de eyección y tiempo diastólico. En parado disminuye la variabilidad del tiempo diastólico y aumenta para la presión sistólica. Durante el ejercicio disminuye la variabilidad del tiempo diastólico, el periodo de pre - eyección y el tiempo de eyección, mientras aumenta para la sístole electromecánica, el volumen sistólico, el gasto cardiac0 y la presión arterial. Por análisis espectral. En la respiración controlada disminuye la relación baja / alta de la mayoría de las variables cardiovasculares. En parado la relación baja / alta aumenta en variables como el tiempo diastólico, la sístole electromecánica y la presión diastólica, disminuye para la presión sistólica. E.n el ejercicio la relación baja / alta estándar aumenta y la relación baja / alta amplia disminuye en la mayoría de las variables cardiovasculares. Por análisis log potencia - log frecuencia. Las maniobras disminuyen la pendiente de la regresión con ascenso del intercepto de la mayor parte dlas variables cardiovasculares. El ejercicio es el que produce los mayores cambios. - Por análisis tono entropía. Sólo algunas variabks mostraron cambios por este tipo de análisis. En respiración controlada disminuye el tono, con aumento de la entropía para la sístole electromecánica y el tiempo diastólico. En parado aumenta el tono, con disminución de la entropía para la sístole electromecánica, el volumen sistólico, el gasto cardiaco, los indices de contractilidad y la presión diastólica. Durante el ejercicio aumenta el tono, con disminución de la entropía para el periodo de pre - eyección y el tiempo diastólico, disminuye el tono con aumento de la entropía para la sístole electromecánica, el volumen sistólico, el gasto cardiaco, indices de contractilidad y la presión diastólica. - Por mapas de retorno. La regularidad de la variables cardiovasculares aumenta durante las maniobras. Así en respiración controlada aumenta para la mayoría de las variables, en parado sólo el tiempo de eyección, el periodo de pre - eyección y los indices de contractilidad lo hacen; en ejercicio muestran el cambio mencionado el tiempo de eyección, el periodo de pre - eyección y el tiempo diastólico. - Por entropía aproximada. En respiración controlada, disminuye para el tiempo de eyección y para la sístole electromecánica; aumenta para las presiones. En parado, disminuye para el gasto cardiaco y aumenta para el tiempo de eyección, el periodo de pre - eyección y el tiempo diastólico. El ejercicio aumenta la entropía de la mayoría de las variables cardiovasculares. Conclusiones. Por los resultados de los estudios realizados: Las tres técnicas de estimación espectral tuvieron un desempeño similar. Se demuestra que los datos de la frecuencia cardíaca latido a latido computados por el cardiotacógrafo, son intercambiables para los análisis temporal y espectral, con los obtenidos a través del procesamiento del intervalo RK, en todas las maniobras utilizadas. Hay un alto grado de acuerdo entre los indicadores temporales y espectrales de la variabilidad de la presión arterial obtenidos de las dos salidas del Finapres, durante las cinco maniobras Los datos de la frecuencia cardiaca, latido a latido, computados por el Finapres no son intercambiables con los obtenidos a través del procesamiento del ECG, para ninguna de las maniobras utilizadas. Se demuestra que una serie de maniobras protocolizadas, determinan un comportamiento característico en algunos de los parámetros temporales y espectrales de la VFC. Los estimadores temporales y espectrales de la VFC a las cinco maniobras impuestas son repetibles, al menos en tres días. El estímulo hiperglucémico determina aumento en la actividad parasimpática al nodo sinusal, mostrada por los indicadores del análisis espectral del intervalo R - R, no atribuible a influencias del centro respiratorio y la disminución ligera en la actividad autonómica simpática al músculo liso arteriolar (disminución de la presión diastólica). El estímulo hipoglucémico determina un ligero aumento en la actividad autonómica simpática e inhibición de la parasimpática sobre el nodo sinusal, mostrada por los indicadores de los análisis temporal, espectral y tono - entropía y un ligero aumento de la actividad simpática al músculo liso arteriolar El estímulo hiperoxémico de corta duración determina un aumento de la actividad parasimpática y disminución de la simpática al nodo sinusal, sin cambio en el flujo autonómico al músculo liso arteriolar, como lo reflejan los indicadores de los análisis temporal y espectral. El estímulo hipoxémico de corta duración determina el aumento en la actividad simpática, junto con una disminución concomitante de la parasimpática al nodo sinusal y disminución I, de la actividad simpática al músculo liso arteriolar, reflejada por los indicadores de los análisis temporal, espectral y tono - entropía. Las variables cardiovasculares presentan variabilidad latido a latido. Parte importante de ésta es determinada por la variabilidad de RR, pa.rte es causada por la respiración. Los mismos factores que determinan la variabilidad de RR, es decir, el balance simpático - vagal, influyen en la variabilidad del resto de las variables cardiovasculares. La respiración influye por mecanismos autonómicos y mecánicos. La variabilidad es modificada por las maniobras empleadas en el estudio de manera determinística, es decir, existe un patrón específico de respuesta como lo muestran los indices de los análisis temporal, espectral, log potencia - log frecuencia, tono - entropía, mapas de retorno y entropía aproximada.